Internal Control Practices for Fraud Prevention in Higher Education: Praktik Pengendalian Internal untuk Pencegahan Penipuan di Perguruan Tinggi - Astriani, Cindy; Hanun, Nur Ravita (Indonesian Journal of Education Methods Development, 2025)
Background: Fraud remains a persistent concern in higher education, especially where internal control practices are weak and organizational behavior shapes the control environment. Specific Background: Two accredited private universities—Melati and Mawar—demonstrate varied cultural and behavioral dynamics influencing their control systems. Knowledge Gap: Previous studies emphasize structural and technical controls, while behavioral and cultural dimensions remain underexplored. Aim: This study analyzes how internal control is implemented for fraud prevention by examining organizational culture, individual behavior, and critical supporting and inhibiting factors. Results: Findings show that integrity, coordinated functions, digital systems, segregation of duties, and routine audits strengthen internal control, whereas limited human resources, weak sanction enforcement, resistance to audits, and incomplete system integration hinder effectiveness. Novelty: The study offers a comparative approach emphasizing behavioral and cultural dimensions supported by triangulated qualitative data. Implications: The results provide practical guidance for higher education leaders to strengthen fraud prevention through structural, behavioral, and cultural improvements. Highlights:• Organizational culture shapes internal control practices• Digital systems support fraud prevention• Audit consistency strengthens governance Keyword: Internal Control, Fraud, Organizational Culture, Behavior, Higher Education